Kualitas Layanan Nsw Berdasarkan Persepsi Dan Harapan Pengguna Layanan Di Pelabuhan Tanjung Priok - Puriningsih, Feronika Sekar; Chairunnisa, Chairunnisa (Warta Penelitian Perhubungan, 2010)
The importance of the port services is ideal for supporting the economy has become a commonexpectations. Bureaucratic, widespread practice extortion everywhere, the flow of importedgoods and so on, resulting in economic conditions, Indonesia suffered. An effort toreduce costly economy is removing barriers in the smooth flow of exports and imports ofgoods, from production to sale. VVhen processing services are still done manually, there arestill many obstacles to the free flow of goods, so the demand for goods and services, whichintegrates Harbour. National single window " public policies for the integration of servicesand the harbour. This study aims at identifying and assessing the quality of NSW in TanjungPrick, by considering the extent to which the level of satisfaction and expectations of consumersservices settings in NSW. This study uses three analytical tools. Importance-PerformanceAnalysis (IP A) is used to map the relationship between the interests of service users ( consumers)with the performance of service providers, as well as gaps in the hope of service attributes.Customer Satisfaction Index (CSI) is used to analyze the level of satisfaction of respondentsoverall. Samples are cargo shipping services company portnet users. Based on thisresearch note that the NSW service attribute responsiveness, cooperation and coordinationof response agencies the implementation of NSW. In addition, the attribute service time outscout ships and ship service move / shift needs to be maintained.Key words: National Single V\1ndow, Seruices, Inaportnet.